Dinâmica migratória e reprodutiva de uma espécie reofílica de peixe (Prochilodus costatus) no Alto São Francisco, MG: diferenças entre populações locais e transpostas e implicações para a instalação de um sistema de transposição de peixes na UHE Três Marias - Lopes, João de Magalhães (2017)
This dissertation is the product of a Research and Development project by Cemig/Aneel that encompasses four subprojects. These projects were motivated by existing technical demands regarding the evaluation of the need to promote fish transposition at the Três Marias dam, and a Conduct Adjustment Term (CAT) celebrated with the Public Ministry of the State of Minas Gerais, Brazil, in 2010. The CAT demands that the company elaborate a study on the feasibility of installing a Fish Passage at the dam. In addition to migratory dynamics data of Prochilodu costatus, evaluated by radiotelemetry, subprojects evaluating the genetics (UFMG) and cytogenetics (UFV) of the species, as well as extensive collection of eggs and larvae from the São Francisco basin (PUC-MG) are in progress. The results were divided in to three chapters. In the first chapter, we present the migratory dynamics of P. costatus populations marked in the lotic stretch of the São Francisco River, upstream of the Três Marias dam. The fish marked in this region presented regular and predictable migratory patterns during the study period. In the second chapter, we explore the influence of environmental factors, especially precipitation, phase of the moon and solar cycle, over the beginning of the migratory process. Precipitation and the new moon seemed to act as important environmental triggers for migration. In the third chapter, we seek to answer the question asked in the CAT signed by the company of whether a Fish Passage is necessary at the Três Marias dam. In this chapter, the data from the migratory dynamics, observed for fishes transposed to the Três Marias dam and to the lotic stretches of the São Francisco River upstream to the dam, were aggregated in order to compare the patterns demonstrated by each group of transposed fish. The results showed that the migratory patterns of the transposed fish differ from those presented by local populations and that the ecological function of a Fish Passage, being the maintenance of feasible and functional populations, will not be reached with its installation. The need for the Fish Passage was also evaluated from the theoretical perspective, based on existing literature.